Outcome of Olecranon Fracture Treated with Tension Band Wiring Versus Anatomical Locking Plate Fixation - Muhammad Inam, Wajid Rehan, Muhammad Kamran Shafi, Muhammad Afaque Alam, Syed Abdur Rub Abidi, Usman Ali, Tauseef Raza, Abdulakbar (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Up to 10% of all upper limb fractures involve the olecranon, and this type of fracture is the most common osseous injury of the elbow joint. These show a bimodal distribution occurring in younger patients due to high-energy trauma and in elderly cohorts with low bone quality after low-energy falls. Objective: To compare functional outcome of tension band wiring versus anatomical locking plate fixation for reduction of olecranon fracture Materials and Methods: This randomized controlled trial study was conducted in the Department of Orthopedic, Lady Reading Hospital, Medical Teaching Institute Peshawar from December 2022 to June 2023. Non-probability consecutive sampling technique was used in this study. Sample size was calculated using WHO calculator keeping 95% confidence interval 80 % power of study, 10% absolute precision, mean Mayo elbow score was 84.0±9.3 in the TBW group and 88.3±9.1 in the locking plate fixation group (4). Expected sample size is 32 patients in each group, total 72 patients. Patients of both genders have age range from 20 to 70 year with Mayo type 2A olecranon fractures, more than 2 mm of joint displacement determined on X-ray elbow, and elbow extension loss determined on physical examination presented within 7 days of the injury were included in the study while Patients with open fracture and revision surgery were excluded from the study. Results: In this study age distribution among 72 patients was analyzed as n= 20-30 Years 17(27.4%) 31-40 Years 14(22.6%) 41-50.Years 11(17.7%) 51-70 Years 20(32.3%). Mean age was 47.1 Years with SD ± 2.87. Gender wise Distribution among 72 Patients was analyzed as Male were 31(50.0%) and female were 31(50.0%). Distribution of duration of disease among 72 patients were analysed as n= 1-2 weeks were 47(75.8%) and 3-4 weeks were 15(24.2%) Practical Implication: There are no established guidelines for the treatment of olecranon fracture in our institution. Most olecranon fractures are treated according to surgeon preferences and surgical experience of the surgeon. Previous studies showed variables results with no consensus. We will provide rationale basis for universal use of standard treatment of olecranon fracture. Conclusion: Although there were no statistically significant differences in clinical outcomes between the two groups, the ALP group had a higher proportion of any complication than the RP group. Keywords: Anatomical locking plate; complications; eyelet wire; olecranon fracture; tension band wiring.